An investigation on the heat transfer model for immersed horizontal tube bundles in a pressurized fluidized bed. (April 2020) - Bao, Zhongkai; Duan, Lunbo; Wu, Ke; Zhao, Changsui
Highlights: Applicability of different dense phase heat transfer models were analyzed. A modified heat transfer model was presented for pressurized fluidized beds. The absolute average percentage deviation of the model predictions was 10.25%. Data points include particle diameters 240–700 μm with pressures 0.1–1.6 MPa. The heat transfer influence rules of parameters were described from the model. Abstract: In order to predict the heat transfer coefficient between the immersed horizontal tube bundles and the pressurized fluidized bed, different types of heat transfer models research process for the horizontal tube surface are presented. The accuracy of these models has been analyzed with the data of pressurized experiments, which indicates the limitation of these models in the application of pressurized fluidized bed. A new semi-empirical emulsion renewal model is proposed which takes the advantages of thermal contact resistance model and heat penetration model into account and modifies the correlation for gas convection heat transfer calculation at elevated pressure. The total experimentally reported 89 points from different sources with pressures ranging 0.1–1.6 MPa, particle diameter 240–700 μm are predicted within the absolute average deviation of 10.25%, which is much lower compared with other models for the same data. The satisfactory description for the influence rule of bed pressure, temperature, gas velocity and particle diameter on the heat transfer coefficient was also given from the model.